Crosstalk Between ER Stress, Autophagy and Inflammation - Chipurupalli, Sandhya; Samavedam, Unni; Robinson, Nirmal (Frontiers in Medicine, 2021)
The endoplasmic reticulum (ER) is not only responsible for protein synthesis and folding but also plays a critical role in sensing cellular stress and maintaining cellular homeostasis. Upon sensing the accumulation of unfolded proteins due to perturbation in protein synthesis or folding, specific intracellular signaling pathways are activated, which are collectively termed as unfolded protein response (UPR). UPR expands the capacity of the protein folding machinery, decreases protein synthesis and enhances ER-associated protein degradation (ERAD) which degrades misfolded proteins through the proteasomes. More recent evidences suggest that UPR also amplifies cytokines-mediated inflammatory responses leading to pathogenesis of inflammatory diseases. UPR signaling also activates autophagy; a lysosome-dependent degradative pathway that has an extended capacity to degrade misfolded proteins and damaged ER. Thus, activation of autophagy limits inflammatory response and provides cyto-protection by attenuating ER-stress. Here we review the mechanisms that couple UPR, autophagy and cytokine-induced inflammation that can facilitate the development of novel therapeutic strategies to mitigate cellular stress and inflammation associated with various pathologies.